2011
DOI: 10.2147/ijn.s25044
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and biocompatibility of a polymer-paclitaxel conjugate for cancer treatment

Abstract: Background Poly(L-γ-glutamylglutamine) paclitaxel (PGG-PTX) conjugate is a non-diblock polymeric drug nanoparticle intended to improve the therapeutic index of paclitaxel. The purpose of the present study was to elucidate further the physicochemical properties of PGG-PTX in order to proceed with its clinical development. Methods and results PGG-PTX was designed by integration of a hydrophobic paclitaxel conjugate through an added hydrophilic glutamic acid onto poly(L-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In U-87 MG cells, FONPs–PTX showed a lower inhibition of cell survival (concentration that inhibits 50% of cell survival IC 50 = 2.5 ± 0.1 μM) than PTX alone (IC 50 = 10.8 ± 1.6 nM), suggesting a delayed effect of the conjugate because of the time needed for intracellular enzymes to cleave PTX from nanoparticles, as previously observed. 79 Gomez et al have recently shown that PTX-coupled nitrogen-doped carbon nanodots by an ester bond exhibit a better anticancer activity compared to free PTX in several cell lines. 59 In our work, we demonstrated that PTX is not released from the prodrug in biological medium at 37 °C.…”
Section: Resultsmentioning
confidence: 99%
“…In U-87 MG cells, FONPs–PTX showed a lower inhibition of cell survival (concentration that inhibits 50% of cell survival IC 50 = 2.5 ± 0.1 μM) than PTX alone (IC 50 = 10.8 ± 1.6 nM), suggesting a delayed effect of the conjugate because of the time needed for intracellular enzymes to cleave PTX from nanoparticles, as previously observed. 79 Gomez et al have recently shown that PTX-coupled nitrogen-doped carbon nanodots by an ester bond exhibit a better anticancer activity compared to free PTX in several cell lines. 59 In our work, we demonstrated that PTX is not released from the prodrug in biological medium at 37 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro stability and drug release studies demonstrated that PTX was not released from the PDC adduct in biological mediums at 37 °C; rather, a sharp PTX release was observed at lower pH values (tumor microenvironment). Thus, we expected that the ester bond will break between PTX and CPP after cellular uptake, and the pharmacological properties of PTX on the microtubular network will not alter after its release . Therefore, we investigated the subcellular localization, intracellular delivery of the drug, the receptor-binding potential of the peptide, and the apoptosis-inducing pathway of our designed PDC in U87MG cells by using Cy5.5-PDC.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we expected that the ester bond will break between PTX and CPP after cellular uptake, and the pharmacological properties of PTX on the microtubular network will not alter after its release. 45 Therefore, we investigated the subcellular localization, intracellular delivery of the drug, the receptor-binding potential of the peptide, and the apoptosis-inducing pathway of our designed PDC in U87MG cells by using Cy5.5-PDC. The cells were treated with 10 nM Cy5.5-PDC for 1 h, washed with ice-cold PBS, further incubated for 4 h, and stained with Hoechst-33258 before images were acquired by an optical microscope.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The obtained PTX-MN nanoparticles were characterized by infrared spectroscopy (Figure 3). The main infrared peaks of the PTX were registered at 3415-3310 cm −1 (N-H stretching vibrations), 2938 cm −1 (methylene stretching vibration), 1720 cm −1 (C=O stretching vibration of the ester groups), 1648 cm −1 (amide I), 1372 cm −1 (the C-N vibrations), 1071 cm −1 (C-O stretch), 982 cm −1 and 706 cm −1 (aromatic bonds) [26,27]. The FTIR spectrum of MN showed the characteristic bands for biotinylated N-palmitoyl chitosan at 3440 cm −1 (O-H, N-H stretch, imidazole ring of biotin), 2919 cm −1 and 2853 cm −1 (methylene and methyl groups stretching vibrations from palmitoyl chain), 1640 cm −1 and 1549 cm −1 (amide I), 1379 cm −1 (the C-N vibrations), 1067 cm −1 (C-O stretch) and for magnetite at 577 cm −1 (specific region for the Fe-O group).…”
Section: Composition and Thermal Behaviormentioning
confidence: 99%